On the structural, mechanical, and biodegradation properties of HA/β‐TCP robocast scaffolds. Issue 7 (7th May 2013) - Houmard, Manuel; Fu, Qiang; Genet, Martin; Saiz, Eduardo; Tomsia, Antoni P.
<x xml:space="preserve">Abstract</x> Hydroxyapatite/β‐tricalcium phosphate (HA/β‐TCP) composite scaffolds have shown great potential for bone‐tissue engineering applications. In this work, ceramic scaffold with different HA/β‐TCP compositions (pure HA, 60HA/40β‐TCP, and 20HA/80β‐TCP) were fabricated by a robotic‐assisted deposition (robocasting) technique using water‐based hydrogel inks. A systematic study was conducted to investigate the porosity, mechanical property, and degradation of the scaffolds. Our results indicate that, at a similar volume porosity, the mechanical strength of the sintered scaffolds increased with the decreasing rod diameter. The compressive strength of the fabricated scaffolds (porosity ≈ 25–80 vol %) varied between ∼3 and ∼50 MPa, a value equal or higher than that of human cancellous bone (2–12 MPa). Although there was a slight increase of Ca and P ions in water after 5 month, no noticeable degradation of the scaffolds in SBF or water was observed. Our findings from this work indicate that composite calcium phosphate scaffolds with customer‐designed chemistry and architecture may be fabricated by a robotic‐assisted deposition method. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 101B: 1233–1242, 2013.